2005
DOI: 10.1103/physrevlett.95.256102
|View full text |Cite
|
Sign up to set email alerts
|

One-DimensionalPtO2at Pt Steps: Formation and Reaction with CO

Abstract: Using core-level spectroscopy and density functional theory we show that a one-dimensional (1D) oxide structure forms at the steps of the Pt(332) surface after exposure. The 1D oxide is found to be stable in an oxygen pressure range, where bulk oxides are only metastable, and is therefore argued to be a precursor to the Pt oxidation. As an example of the consequences of such a precursor exclusively present at the steps, we investigate the reaction of CO with oxygen covered Pt(332). Albeit more strongly bound, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
124
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(141 citation statements)
references
References 20 publications
15
124
0
2
Order By: Relevance
“…The binding energy of peak (F) in the C 1s region is consistent with assignment to CO adsorbed at on-top sites on metallic Pt particles. [33][34][35][36] Furthermore, the occurrence of peak (V) as a shifted component of peak (IV) is consistent with the core level shift due to CO adsorption. 35,36 In Fig.…”
Section: The Adsorption Of Co On a 25% Pt-ceo 2 Mixed Oxidesupporting
confidence: 79%
“…The binding energy of peak (F) in the C 1s region is consistent with assignment to CO adsorbed at on-top sites on metallic Pt particles. [33][34][35][36] Furthermore, the occurrence of peak (V) as a shifted component of peak (IV) is consistent with the core level shift due to CO adsorption. 35,36 In Fig.…”
Section: The Adsorption Of Co On a 25% Pt-ceo 2 Mixed Oxidesupporting
confidence: 79%
“…Using the relative kinetic energies of the Pt and bulk-W 4f7/2 features (35.86 ± 0.01 and 55.85 ± 0.01 eV, respectively), the difference in photon energies (20 eV), and the bulk-W 4f7/2 BE of 31.41 ± 0.01 eV [44], we obtain a BE of 71.40 ± 0.02 eV for ML Pt/W(110). Using reported values of the bulk Pt BE [45][46][47][48][49][50][51][52][53][54][55][56][57][58] we ascertain a value of 70.94 ± 0.08 eV for the BE of bulk Pt, yielding a core-level shift of +0.46 ± 0.09 eV for the Pt monolayer. We do not observe any shift in the Pt BE that might be associated with the transformation from the ps to the cp phase.…”
Section: Results and Analysismentioning
confidence: 99%
“…One reason for this behavior could be that the particles contains a larger number of defects such as steps, kinks and corners which are sites considered as beneficial for oxidation [59]. Indeed, lately it has been observed that one dimensional oxides may easily form at steps at UHV conditions containing under coordinated atoms on vicinal surfaces [60,61]. In fact, it has been shown that the exact structure of the 1D oxide on the steps determines the rate of the continued growth of a 2D surface oxide [62].…”
Section: Calculated Core Level Shiftsmentioning
confidence: 99%